The Effects of Employee-Customer Interactions in Customer Retention on Jollibee Big-R Robinson at Brgy. Pasong Putik, Novaliches, Quezon City Mary Eimyreh Obligar: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Customer retention is the ability of a business to transform one-time clients into patroncustomers and keep them from switching to a rival. Employee-customer interaction is aconnection formed between the employee and the customer in a food establishment.Employee-customer interaction affects a business's customer retention.The result of this study shows that the majority of the respondents are female in the age groupof 19 to 30 years old, with a percentage of 56%. It implies that adults want food that is tasty,and elders are more conscious of their health than adults. The results of this study show thatthe problem encountered by employees in having customer retention was food quality; thismeans that most of the respondents are satisfied with the taste and flavor of the food, and itaffects the satisfaction of the customers. The respondents assess the effects of employee-customer interaction in terms of customer complaints when the employees offer solutions tothe problems; this means that discussing solutions helps businesses provide good customerservice.This study recommends the company continue to serve food that is flavorful and tasty andconduct product development to satisfy customers and increase sales. The employees shouldpractice more in handling customer complaints as it will help the business provide greatcustomer service and retain customers.
Keywords: Hospitality Management